2014
DOI: 10.4103/0259-1162.128895
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ropivacaine caudal analgesia using dexamethasone or magnesium in children undergoing inguinal hernia repair

Abstract: Background:Caudal analgesia is the most commonly used technique providing intra- and postoperative analgesia for various pediatric infraumbilical surgical procedures but with the disadvantage of short duration of action after single injection. Caudal dexamethasone and magnesium could offer significant analgesic benefits. We compared the analgesic effects and side-effects of dexamethasone or magnesium added to caudal ropivacaine in pediatric patients undergoing inguinal hernia repair.Materials and Methods:A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 42 publications
(53 reference statements)
0
51
0
1
Order By: Relevance
“…Several studies suggested that the addition of dexamethasone through caudal route[16] or IV route[12171819] as an adjuvant to RA significantly reduced the post-operative pain by prolonging the duration of analgesia with significantly lesser analgesic consumption. Our study results are in line with this, in which we demonstrated that the addition of dexamethasone through caudal or IV route could significantly prolong the mean time to first rescue analgesic with the significant advantage of caudal over IV route in children undergoing inguinal hernia repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggested that the addition of dexamethasone through caudal route[16] or IV route[12171819] as an adjuvant to RA significantly reduced the post-operative pain by prolonging the duration of analgesia with significantly lesser analgesic consumption. Our study results are in line with this, in which we demonstrated that the addition of dexamethasone through caudal or IV route could significantly prolong the mean time to first rescue analgesic with the significant advantage of caudal over IV route in children undergoing inguinal hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…[1620] Even the systemic administration of steroids has to be effective for reducing post-operative pain, but the results are inconclusive. [8212223]…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] The combination of ropivacaine and both particulate and non-particulate steroid agents, has been used for both various spinal and musculoskeletal diagnostic and therapeutic injections, with reports in the literature of such combinations being used for pain injections and infusions. [25][26][27][28][29][30] The combination of concern is that of ropivacaine and alkaline solutions, a category that dexamethasone sodium phosphate falls into with a pH of 8.0. This has been previously described in the literature when evaluating alkalising local anaesthetic agents, with reports of ropivacaine precipitating at a pH of 6.0 and above.…”
Section: Discussionmentioning
confidence: 99%
“…The time of first analgesic request was significantly longer in magnesium groups (500 ± 190 min) compared with ropivacaine group (260 ± 65 min). Ropivacaine group patients achieved significantly higher Children's Hospital of Eastern Ontario Pain Scale and Faces Legs Activity Cry CONSOL ability scores (4th hourly) compared with magnesium group (8th hourly) (17) . In contrast to our study Birbicer et al, compared bupivacaine 0.5% plus 50 mg magnesium to bupivacaine 0.5% alone for caudal anesthesia in children.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested that epidurally administered magnesium as an adjuvant to local anesthetics could reduce the postoperative pain in adults. But few studies are available about its use as an adjuvant in caudal block for such purpose (5) . We designed this study to compare the intensity, safety and duration of postoperative pain relief using caudal magnesium sulfate as adjuvant with isobaric bupivacaine 0 .5% in pediatric patients undergoing lower abdominal surgeries.…”
Section: Introductionmentioning
confidence: 99%